Investigation of Student Satisfaction with Dance Courses : Expectations and Responsibility. - Michaelson, Samantha; Bergstrom, Brent (My University, 2009)
This project was a preliminary exploration of surveys addressing student satisfaction with dance classes. Throughout the project, the dance program at the University of Wisconsin--Eau Claire was compared to six area schools of equivalent minor programs. These included schools in both Wisconsin and Minnesota. The goal of this project was to see what is lacking in the program at the University of Wisconsin--Eau Claire and what our program has that other schools have overlooked.
Color poster with text, images, and graphs describing research conducted by Samantha Michaelson and Brent Bergstrom, advised by Toni Poll-Sorensen.
Keywords: Dance--Study and teaching (Higher)--Evaluation; Dance--Study and teaching (Higher)--Wisconsin; Dance--Study and teaching (Higher)--Minnesota; University of Wisconsin--Eau Claire. Dept. of Music and Theatre Arts--Students--Attitudes; Dance students--Wisconsin--Attitudes; Dance students--Minnesota--Attitudes; Posters